2020
DOI: 10.21203/rs.3.rs-15695/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Migrants’ and refugees’ health status and healthcare in Europe: A scoping literature review

Abstract: Abstract Background There is increasing attention paid to the arrival of migrants from outwith the EU region to the European countries. Healthcare that is universally and equably accessible needs to be provided for these migrants throughout the range of national contexts and in response to complex and evolving individual needs. It is important to look at the evidence available on provision and access to healthcare for migrants to identify barriers to accessing healthcar… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 23 publications
3
35
0
1
Order By: Relevance
“…The breadth of vaccine access barriers -practical, legal, and administrative -experienced by migrants and identified in this review were significant. Migrants' barriers to accessing healthcare are already well documented (91)(92)(93)(94), and this review confirms their role in limiting vaccine uptake. This included barriers from gaps in healthcare provider knowledge around catch-up vaccination, an area where experts have called for more guidelines.…”
Section: Discussionsupporting
confidence: 66%
“…The breadth of vaccine access barriers -practical, legal, and administrative -experienced by migrants and identified in this review were significant. Migrants' barriers to accessing healthcare are already well documented (91)(92)(93)(94), and this review confirms their role in limiting vaccine uptake. This included barriers from gaps in healthcare provider knowledge around catch-up vaccination, an area where experts have called for more guidelines.…”
Section: Discussionsupporting
confidence: 66%
“…The breadth of vaccine access barriers—practical, legal, and administrative—experienced by migrants and identified in this Review was substantial. Migrants' barriers to accessing health care are already well documented, 97 , 98 , 99 , 100 and this Review confirms their role in limiting vaccine uptake. Our findings align with a recent rapid review of vaccine hesitancy in migrants, 101 which suggested that hesitancy in these populations might be an expression of cultural alienation resulting from experiences of marginalisation or discrimination, while a systematic review 102 of mostly US studies concluded that vaccination campaigns might need special consideration among this population due to the specific cultural and knowledge barriers identified.…”
Section: Discussionsupporting
confidence: 62%
“…Whether bias in delivery type occurred related to the high number of migrants was not explored. A recent review of healthcare in 9 European countries including France showed that, despite equitable aspirations, inequalities between migrants and non-migrants in health and in access to healthcare services persist 2…”
Section: Commentarymentioning
confidence: 99%